(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background : Intrauterine Fetal Death (IUFD) is one of the most distressful condition in a woman’s life. It causes emotional breakdown, psychological upset and time related risk like DIC compel to induce labour instead of waiting for spontaneous onset. Recently as LSCS rate is increasing, we find more cases of IUFD with previous history of LSCS. In IUFD journey of labour is fruitless, so we want to terminate the pregnanancy vaginally even in scarred uterus to reduce mental trauma, physical morbidity and to decrease repeat LSCS rate. But there is fear of scar dehiscence, scar rupture in induction of labour in scarred uterus. So we want to see outcome of combination of mifepristone and misoprostol in the management of IUFD as it is one of the major advances in modern clinical practice with safety and efficacy. Mifepristone causes decidual separation and increases the sensitivity of misoprostol to myometrium and misoprostol increases uterine contractility. Thus combined regimen shortens the induction to delivery interval which is very necessary in IUFD cases as women are often keen for a quick resolution and delivery. To evaluate the outcome of combined use of Mifepristone and Misoprostol in induction of labour in IUFD with previous history of Lower Segment Caesarean Section (LSCS) at Chittagong Medical College Hospital (CMCH). Materials and methods: This was prospective clinical trial study and was conducted in Department of Obstetrics & Gynecology of CMCH from April 2021 to September 2021. During the study period 50 patients presenting with IUFD with previous history of LSCS were taken as study subjects. After getting written informed consent Tab. Mifepristone (200mg) was given 8 hourly for 48 hours (6 doses). Then patient was being waited for another 48 hours. If labour pain not start, then Tab. Misoprostol (25 µg) was given per vaginally 6-8 hourly maximum 4 doses in 24 hours. All the information was recorded according to fixed protocol. Collected data were classified, edited, coded and entered into the computer for statistical analysis by using SPSS version 23. Results: Out of 50 patients, the mean age was 28.3±6.4 years. Patients with previous history of 1 LSCS were 45 (90.0%) and 2 LSCS were 5 (10.0%). After combined use of mifepristone and misoprostol, majority 32(64.0%) patients need induction to delivery interval within 120 hrs, out of which most of the patients 23(46.0%) delivered within 96-110 hours. 96.0% patients gave vaginal birth and 4.0% patients needed caesarean section. Regarding maternal complication, PPH was found in 3(6.0%) cases and retained placenta 3(6.0%) cases which could be controlled effectively. No case of scar rupture was found. Primary outcome: Induction to delivery interval, Secondary outcome: Assessment of complication of induction and Assessment of failure rate after induction. Conclusion: Combination of mifepristone and misoprostol appeared to be more effective in comparison to existing regimens like misoprostol alone or oxytocin or mechanical balloon catheter for induction of labour in cases of IUFD with scarred uterus and the regimen was safe, easy to administer and affordable to the patients. JCMCTA 2024 ; 35 (2) : 150-155